Pancytopenia associated with Weissella confusa septicemia - Akkus, Canan; Arslan, Abdulhamid (The Journal of Infection in Developing Countries, 2026)
Introduction: Weissella spp. are facultative gram-positive bacteria. They are also part of the human microbiota and can cause opportunistic infections. There are very few case reports in the literature describing bacteremia caused by W. confusa. Case presentation: A 74-year-old male patient presented to the Internal Medicine Department of Ankara Etlik City Hospital with complaints of fever, chills, nausea, and vomiting. Laboratory tests revealed pancytopenia. Etiological investigation identified W. confusa in blood cultures using MALDI-TOF MS, and other potential causes of pancytopenia were excluded. The patient had chronic kidney disease and was undergoing hemodialysis three times a week. Conclusions: W. confusa should be considered among opportunistic pathogens, especially in patients with end-stage renal disease. This case is presented as a rare clinical report due to the association of pancytopenia with W. confusa septicemia.